A longitudinal study of electrical stimulation levels and electrode impedance in children using the Clarion cochlear implant. - Henkin Y; Kaplan-Neeman R; Kronenberg J; Migirov L; Hildesheimer M; Muchnik C (Acta Oto-Laryngologica, 2006)
Conclusions. Electrical stimulation levels and electrode impedance values (EIVs) in children using the Clarion cochlear implant (CI) programmed with CIS strategy stabilized after 3 months of implant use. The data presented here may be useful as a general guideline for the programming of infants and young children and may further be of help for the identification of patients who fall outside the 'average' range. Objectives. The purpose of the present study was to evaluate changes in electrical stimulation levels, i.e. threshold (T) levels, comfortable (M) levels, dynamic range (DR), and EIVs during the first 18 months of implant use, in children using the Clarion CI. Materials and methods. The maps of 18 pre-lingual children (mean age at implantation 4.2 years; range 1-8), using the Enhanced Bipolar 1.2 or Bipolar standard electrode with the S-Series speech processor programmed with CIS strategy, were examined at five time points: connection, and 3, 6, 12, and 18 months post-initial stimulation. T levels, M levels, DR and EIVs were analyzed according to four cochlear segments: apical, apical-medial, medial-basal, and basal. Results. During the first 3 months of implant use T levels increased to some extent, whereas M levels and DR increased significantly. From 3 months and through the entire follow-up, T and M levels as well as DR were stable. EIVs of current carrying electrodes decreased significantly from connection to the 3-month visit; thereafter a stabilization of values was evident. Electrical stimulation levels and EIVs did not differ among the cochlear segments during the entire follow-up.